MSW: From pollution/degradation source to resource - Pirlone, Francesca; Candia, Selena (TeMA - Journal of Land Use, Mobility and Environment, 2016)
Municipal Solid Waste is one of the biggest challenges that cities are facing: MSW is considered of the main sources of energy consumption, urban degradation and pollution. This paper defines the major negative effects of MSW on cities and proposes new solutions to guide waste policies. Most contemporary waste management efforts are focused at regional government level and based on high tech waste disposal by methods such as landfill and incineration. However, these methods are becoming increasingly expensive, energy inefficient and pollutant: waste disposal is not sustainable and will have negative implications for future generations. In this paper are proposed all the principle solutions that could be undertaken. New policy instruments are presented updating and adapting policies and encouraging innovation for less wasteful systems. Waste management plans are fundamental to increase the ability of urban areas to effectively adapt to waste challenges. These plans have to give an outline of waste streams and treatment options and provide a scenario for the following years that significantly reduce landfills and incinerators in favor of prevention, reuse and recycling. The key aim of an urban waste management plan is to set out the work towards a zero waste economy as part of the transition to a sustainable economy. Other questions remain still opened: How to change people’s behavior? What is the role of environmental education and risk perception? It is sure that the involvement of the various stakeholders and the wider public in the planning process should aim at ensuring acceptance of the waste policy.